PENGEMBANGAN BUKU PANDUAN MENULIS KARANGAN DESKRIPSI BERBASIS GO TO YOUR POST PADA SISWA KELAS V SD - Hafni Kharismawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The study aimed to develop a descriptive essay writing guidebook. The method of this study was R&D (Research and Development) with the research design of Borg and Gall modified by Sugiyono. The result of this study was a descriptive essay writing guide book based on go to your post. Based on the result of the feasibility test  by the media experts, the book was feasible with an average value of 79%. Then, the results of validation by material experts obtained that the product was very feasible with an average value of 87.31%. Moreover, the results of the validation by linguists found that the guide book was appropriate with an average value of 76%. Finally, the results of students’ response questionnaire on the limited trial obtained an average value of 92% with Very Good criteria. Based on these results, the final product of the guide book for writing descriptive essay based on go to your post was declared suitabel  to be used in the learning activities for grade 5 elementary school students.